PERFORMANCE OF SALES PERSON IN A SMARTPHONE MARKET IN TURKEY - Telli Yamamoto Gonca; Fehim Düzgün (Фінансово-кредитна діяльність: проблеми теорії та практики, 2018)
Smartphone market is growing very quickly with embedding new technologies. Many global and local brands are entering aggressively to Turkish market. In Turkey, there are different channels for this business; technology superstores’, telecom retailer and mix retail channel. Mainly 3 technology chains have around 200 important shops. Telecom retail channel has around 8.000 shops with different operators and different owners which needs long-term investment, Mix channel also has around 11.000 independent stores which needs high field force investment to contact with all independent dealers. We may say that technology superstores seems more suitable for fast growing brands, Because technology superstore channel has only 200 stores with high capacity which can be controllable more easily.